PWVD Resolution Considerations for LFMCW Signal Detection by WHT - Gulum, Taylan O.; Erdogan, A. Yasin; Guner, Kani K.; Durak-Ata, Lutfiye; Yildirim, Tulay; Pace, Phillip E. (IEEE, 2014)
Linear Frequency Modulated Continuous Waveform (LFMCW) is one of the most common waveforms used in low probability of intercept (LPI) radars. The Wigner-Hough transform (WHT) is a powerful technique for detection and parameter extraction of LFMCW waveforms that can be employed by Electronic Support Receivers. For a fast detection and a timely response to the adversary emitter, the selection of the pseudo Wigner-Ville distribution (PWVD) window length is critical. In this work we analyze the relation between PWVD window length, WHT span angle and span resolution. It is shown that faster correct detections can be achieved by decreasing the PWVD window length and consequently decreasing the WHT plane. A rapid detection and apiori estimation of target emitter signal chirp rate will allow enough time for a fine tuned post-processing which can be applied specifically to the a priori estimates.
Keywords: Pseudo Wigner Ville Distribution; PWVD; LPI; FMCW; Wigner-Hough Transform; ESR; Electronic Support Receiver; Computer Science; Physics; Telecommunications